Renal replacement therapy for children throughout the world: the need for a global registry - Amstel, Sophie Ploos van; Schaefer, Franz (Pediatric nephrology, 2018)
BackgroundTo describe the factors affecting the incidence of renal replacement therapy (RRT) among children, information from RRT registries is required. We aimed to give an overview of existing pediatric RRT registries worldwide, identify regions with a need to commence or increase data collection on pediatric RRT, and provide a rationale for developing a global RRT registry.MethodsA survey assessing pediatric RRT registry status was sent to International Pediatric Nephrology Associateion (IPNA) members in 127 countries in January 2016. The survey was complemented by a systematic literature search for active pediatric RRT registries.ResultsComplete survey responses were retrieved from 94 countries (representing 86.2% of the world childhood population), with 84 (81.2%) having the means to provide RRT to children, given that there are no other limitations such as financial, social, or religious restraints. Fifty-one (35.3%) countries had national registries for both dialysis and transplantation, nine (30.0%) either had a dialysis or a transplant registry, six participated in international registries only (2.7%), and in 18 (13.2%), children on RRT were not followed in any registry. The search identified 92 pediatric RRT registries, primarily national registries located in Europe, North America, and Asia.ConclusionsAlthough pediatric RRT can be provided in 84 countries representing 81.2% of the world’s childhood population, national pediatric RRT registries are unavailable in many countries. To improve knowledge about the incidence and outcomes of pediatric RRT around the globe, an international population-based pediatric RRT registry has recently been initiated.
Published online: 22 December 2017
Gesehen am 06.06.2018